Is there a risk of developmental problems in infants born to mothers with gestational diabetes mellitus and/or pre-eclampsia? - Bilge Nur Yardımcı-Lokmanoğlu; Yusuf Topal; Esra Kınacı-Biber; Zeynep Arıkan; Gülsen Sırtbaş-Işık; Doğan Porsnok; Hasan Tolga Çelik; Akmer Mutlu (PLoS ONE, 2025)
Objective The aims of this study were (i) to describe the early spontaneous movements in 3-to 5-month-old infants in groups of infants born to mothers with GDM and/or PE, (ii) to compare them, and (iii) to analyze the differences between infants with these risk factors and typically developing infants born to mothers without GDM and/or PE and other risk factors. Methods This cohort study included 255 infants in 4 groups: (i) 96 infants born to mothers with GDM, (ii) 78 infants born to mothers with PE, (iii) 31 infants born to mothers with GDM and PE, and (iv) 50 typically developing infants. Early spontaneous movements, including not only fidgety movements but also concurrent movement and postural patterns, were assessed using the General Movements Assessment (GMA), which determines the Motor Optimality Score-Revised (MOS-R). Comparisons were made using one-way ANOVA for normally distributed continuous variables, Kruskal-Wallis test for non-normally distributed data, and Pearson chi-squared for categorical variables. Univariate logistic regression analyses were used to determine the odds ratios (OR) with 95% confidence intervals (CI). Results There were no differences between the three groups, which included infants whose mothers had at least one of these risk factors (p>0.05). Infants born to mothers with GDM, infants born to mothers with PE, and infants born to mothers with both GDM and PE had more aberrant fidgety movements, reduced age-adequate movement repertoire, and more abnormal postural patterns than typically developing infants (p<0.05), in addition to lower MOS-R. When looking at those with ≤24 in MOS-R, the odds ratios were ≥2.74. Conclusion Findings suggest that early spontaneous movements, GMA, may play a crucial role in understanding developmental outcomes of these infants and in determining infants who need early intervention.